The Relationship of Health Worker Support to Dietary Adherence in Type 2 Diabetes Mellitus Patients - Safruddin; Munir, Nur Wahyuni; Putri, Helmalia (Omni Nursing Journal, 2025)
Background: Diabetes Mellitus (DM) is a metabolic disorder characterized by hyperglycemia, which occurs due to impaired insulin secretion, insulin resistance, or both. Poor dietary adherence in type 2 DM patients increases the risk of complications and worsens quality of life. Objective: The purpose of this study was to determine the relationship between health worker support for the dietary adherence of type 2 diabetes mellitus patients. Methods: This was an analytical survey with a cross-sectional design involving 67 respondents, determined using the Lemeshow formula. Inclusion criteria were patients diagnosed with type 2 DM by a physician, aged >18 years, and willing to participate, while exclusion criteria included patients unable to communicate and pregnant or breastfeeding women. Health worker support was measured using a validated questionnaire by Rafdinal (2019) (16 items, Cronbach’s α = 0.871), and dietary adherence was assessed using the Dietary Behavior Questionnaire (DBQ) (Aklima, Kritpracha, & Thaniwattananon, 2013) consisting of 16 items (Cronbach’s α = 0.82). Data were analyzed using Chi-square. Results: The study found a significant relationship between health worker support and dietary adherence in type 2 DM patients (p = 0.004). Patients who reported high health worker support were more likely to achieve moderate to high dietary adherence (72%) compared to those with low support (38%). Conclusion: Health worker support significantly influences dietary adherence among type 2 DM patients. Strengthening structured health education, counseling, and collaboration with families is recommended to improve patient compliance and prevent long-term complications.